ASSESSMENT OF WORKING CONDITIONS AT WORKPLACES OF BOBBIN-DISK AND CYLINDER GRINDING MACHINES - Mikhail A. Tamarkin; Mikhail Y. Shcherba (Advanced Engineering Research)
The working conditions at the workplace of the bobbin-disk and cylinder grinding woodworking machines are evaluated. The excess of the standard values of such occupational hazards as dust and noise parameters is stated. The causes of the excess of the real values of noise and dustiness over the standard ones are closely analyzed.